Pengaruh Literasi Kewirausahaan terhadap Intensi Berwirausaha Mahasiswa Pendidikan Ekonomi - Imam Prawiranegara Gani; Esta Larosa; Ardiansyah; Yulianti Toralawe (Jayapangus Press, 2023)
This study aims to determine the effect of entrepreneurial literacy on student entrepreneurial intentions. This research is a quantitative research. This research was conducted at the Faculty of Economics, State University of Gorontalo. The sample of this research was 200 students, the sample was taken using simple random sampling technique. Data collection techniques using a questionnaire. The data analysis technique used is simple regression analysis. The results of this study are that there is a positive and significant influence of entrepreneurial literacy on entrepreneurial intentions, this is shown by the t count of 12.266 and the Sig. 0.000 < α 0.05, it can be stated that Entrepreneurial Literacy has a significant effect on Entrepreneurial Intentions. The value of the effect shows positive, indicating that when entrepreneurial literacy increases, the entrepreneurial intention also increases. Thus it can be concluded that entrepreneurial literacy has a contribution to building entrepreneurial intentions of students of economic education at Gorontalo State University.